To Assess Liraglutide’s Therapeutic Effect in Patients with Type 2 Diabetes Mellitus Using Flash Glucose Monitoring System - Yin J; Han M; Li L; Li Y; Liu Z; Yang J; Liu Y (Diabetes, Metabolic Syndrome and Obesity, 2021)
Jianhong Yin,1,* Minmin Han,1,2,* Linhui Li,3 Yang Li,4 Zi’ang Liu,5,6 Jing Yang,1 Yunfeng Liu1 1Department of Endocrinology, First Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 2First Clinical Medical College, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 3Department of Endocrinology, Taiyuan Central Hospital, Taiyuan, Shanxi, People’s Republic of China; 4Department of Infectious Diseases, Linfen People’s Hospital, Linfen, Shanxi, People’s Republic of China; 5Third Clinical Medical College, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 6The Affiliated Bethune Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Yang; Yunfeng LiuDepartment of Endocrinology, First Hospital of Shanxi Medical University, No. 85 Jiefang Nan Road, Yingze District, Taiyuan, Shanxi Province, People’s Republic of ChinaTel +86 18703416196Fax +86 351-4639758Email yangjlm@126.com; nectarliu@163.comPurpose: Liraglutide, a type of glucagon-like peptide-1 receptor agonist, has significant anti-hyperglycaemic activity without increasing the incidence of hypoglycaemia. In addition, it can improve β-cell function and insulin resistance. The flash glucose monitoring system (FGMS) is a novel method to document consecutive and detailed interstitial glucose levels, further reflecting blood glucose levels. This study aimed to investigate the therapeutic effect of liraglutide on blood glucose management (glucose variability, hyperglycaemia, and the incidence of hypoglycaemia), β-cell function, and insulin resistance in patients with diabetes.Patients and Methods: Thirty-three patients with type 2 diabetes mellitus were recruited in this study. On the basis of metformin monotherapy, these patients received liraglutide add-on treatment for 3 months. The FGMS was used to document glucose levels before and after add-on treatment. Parameters of glucose variability, blood glucose levels at specific time periods, and the incidence of hypoglycaemia were assessed according to FGMS data and compared before and after liraglutide add-on treatment. Further, β-cell function and insulin resistance were assessed and compared before and after liraglutide add-on treatment.Results: According to FGMS monitoring data, liraglutide add-on treatment significantly improved general, within-day, and day-to-day glucose variability and the glucose-target-rate. Further, the specifically analysed blood glucose levels at different time periods showed that blood glucose levels significantly decreased at nocturnal, fasting, and postprandial periods after add-on treatment. The incidence of hypoglycaemia was comparable during the whole day, daytime, and night-time according to the prespecified cutoffs (3.9 mmol/L and 3.0 mmol/L) before and after add-on treatment. Analysis of other assessed parameters revealed significant differences in glycosylated hemoglobin A1c and fasting blood glucose levels as well as parameters of β-cell function and insulin resistance before and after add-on treatment.Conclusion: In type 2 diabetes mellitus, liraglutide treatment can effectively decrease glucose variability and ameliorate hyperglycaemia without increasing the incidence of hypoglycaemia. In addition, liraglutide can significantly improve the β-cell function and insulin resistance.Keywords: glucagon-like peptide-1 receptor agonist, glucose variability, glucose target rate, time in range, β-cell function, insulin resistance